Studying the Relationship of Civil Behavior and Organizational Justice with the Job Satisfaction of Mohaghegh Ardabili University Staff - Soleyman Iranzadeh; Nazel Assadi (مدیریت بهره وری, 2009)
Organizational justice and civil behavior are considered as one of the basic and most important factors in the job satisfaction and performance of the staff of every organization. Therefore, the goal of this study is to determine the contribution of the variables of organizational justice and civil behavior in predicting the job satisfaction of MohagheghArdabiliUniversity staff. The Statistical population consists of all the administrative personnel and the academic staff in the academic year 87-88            (N =380). The study sample included 190 male and female staff of the University based on relative random-stratified sampling.In order to collect data, researcher-made questionnaires-organizational justice questionnaire, civil behavior questionnaire, and job satisfaction questionnaire-were used. The results showed that there is a meaningful relationship between the variables of organizational justice and civil behavior with the job satisfaction of the staff, and both variables have the capabilitiy of predicting job satisfaction, but this capability was higher in the case of the organizational justice. Another finding of the research was that there was not a meaningful difference between the male and female staff with regard to civil behavior. However, there was a meaningful difference between the male and female staff from the viewpoint of organizational justice and jab satisfaction (P <0.0l).